2017
DOI: 10.5222/iksst.2018.029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single-Layer or Double-Layer Closure of the Uterine Incision at Cesarean Section on Uterine Scar Formation

Abstract: ÖZ Amaç

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…26 Some studies suggest that single-layer locking modification may increase the risk of uterine rupture by causing an increase in tissue hypoxia and insufficient healing. 27,28 In a study by Yasmin et al comparing locked and non-locking suturing, it was shown that locked suturing of the first layer resulted in decreased myometrial thickness and increased blood loss. 29 In our study, both the scar and myometrial thickness were found to be higher than the single-layer locking suture technique, other modified Lembert and lateral to medial suture techniques.…”
Section: Discussionmentioning
confidence: 99%
“…26 Some studies suggest that single-layer locking modification may increase the risk of uterine rupture by causing an increase in tissue hypoxia and insufficient healing. 27,28 In a study by Yasmin et al comparing locked and non-locking suturing, it was shown that locked suturing of the first layer resulted in decreased myometrial thickness and increased blood loss. 29 In our study, both the scar and myometrial thickness were found to be higher than the single-layer locking suture technique, other modified Lembert and lateral to medial suture techniques.…”
Section: Discussionmentioning
confidence: 99%